STRUKTUR DAN NILAI-NILAI BUDAYA MINANGKABAU DALAM NASKAH PASAMBAHAN MAANTAAN KAMPIE SIRIAH - Rezza Rukmana; Novia Juita; Hamidin Hamidin (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
The purpose of this article to describe structure and cultural value in Pasambahan Maantaan Kampie Siriah (Propose). The data of this research is structure and cultural value in Pasambahan Maantaan Kampie Siriah (Propose). The analyzing technique has been done with follow procedure: (1) inventaratation of data, (2) transliterate data into Indonesia language, (3) classification of data, (4) analyze by theory, and (5) conclusion. The findings of the research is Pasambahan structure consist are Sambah statement, Pasambahan Siriah, and content of Pasambahan. In the expression structure of sambah statement consist of the opening by guest (P2), obeisance statement by guest (P2) and owner house (P1), obeisance terminate by guest (P2), confirmation by owner house (P1), deferment while (agreement owner house (P1) and guest (P2)). In the expression structure of Pasambahan Siriah consist of the the opening by guest (P2), intention content by guest (P2), confirmation by owner house (P1), and deferment while (agreement owner house and guest). Content of Pasambahan consist of the aim and mean. Cultural values which be contained is humility value and respect for other, agreement value and consensus, fidelity value and accuracy, submissive value and obedient to the custome, the nature of human life, human nature against, and human nature connection peer human. Keywords: structure ,cultural values, pasambahan, maantaankampiesiriah